Protagonismo quilombola: seus sujeitos e seus saberes influenciando a educação - Fonseca, Dagoberto José [UNESP] (Instituto Metodista de Servicos Educacionais, 2014)
This article aims at presenting the quilombola people and their knowledge, as they influence education, as well as and the education that exists in these communities in Brazil, particularly in the state of São Paulo. Furthermore, it tries to explain what are the quilombos, the origin of the term and the political and cultural history of these populations in the country, drawing a time continuum to facilitate the understanding of the reality of these groups and communities in various parts of the country in the XXI century. Thus we will have the opportunity to reflect, discuss and clarify some aspects that guide the reality of the quilombola communities in Brazil, and therefore to expand our critical capacity about the present educational process.

O artigo visou apresentar os sujeitos e os saberes quilombolas que influenciam a educação, bem como a educação existente nestas comunidades no Brasil e em particular no Estado de São Paulo.
Keywords: Leadership; Quilombola; leaders; quilombismo; knowledge; Education; Educação; Quilombo; quilombola; saberes; sujeitos